Schools as Sites of Homelessness Prevention: Learning from Youth Experiences in a Canadian Context - Malenfant, Jayne; Nichols, Naomi (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2025)
Youth homelessness in Canada impacts a significant number of young people. More specific to our focus, populations of young people who are more likely to experience homelessness (e.g. youth with mental health issues, 2SLGBTQIA+ youth, youth from care, and Indigenous youth) face significant barriers to accessing safe, culturally appropriate, and supportive education, suggesting rights to housing and rights to education are intersecting equity issues. This article presents findings from a participatory research project led by members of Youth Action Research Revolution, carried out in Tio’tiá:ke/Montréal, Québec, Canada. Building from experiences young people shared, this article highlights aspects of the public education system that pose problems for youth who are precariously housed or homeless, namely, the application of one-size-fits-all approaches, barriers for students with mental health or learning disability diagnoses, and the lack of clear or actionable institutional mechanisms for students to access preventative support. Following this, we outline educational discourses, practices, and processes that constitute where something may have been done differently to prevent homelessness. We conclude with possible actions to support youth homelessness prevention in schools, including creating more flexible ways for children and families to access supports, resourcing “champion” teachers, and addressing the insidious biases and discrimination in the organization of school policies.